Development of flexibility in 17–18-year-old Savat boxers - Konovalchuk, Anastasiia; Mordyk, Мykola; Bakiko, Ihor; Hrebik, Oleh (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
French Savate boxing is growing in popularity in Ukraine, making the study of physical qualities, such as flexibility, essential for athletic success. Flexibility is a critical factor in executing complex, coordinated strikes in Savate. This study aimed to assess the flexibility levels of 17- to 18-year-old Savate boxers and explore methods to enhance it. The research was conducted at Lesya Ukrainka Volyn National University in Lutsk with ten healthy students aged 17-18, who had 1-2 years of Savate training experience and voluntarily participated with informed consent. The flexibility of the participants was evaluated using tests for shoulder joint mobility, hip joint mobility, and overall flexibility through specific exercises. The study involved theoretical research, practical assessment, and the implementation of an experimental flexibility training method. The results showed significant improvements (p<0.05) in flexibility specific to Savate boxing, leading to better execution of complex strikes such as Chasse frontal, Chasse lateral, and Chasse tournant during sparring sessions. The findings highlight the importance of targeted flexibility training in improving athletic performance in Savate boxing. This experimental method demonstrated effectiveness and has potential for broader application in the training of Savate fighters.